HUBUNGAN MOTIVASI BELAJAR DAN TINGKAT PENGHASILAN ORANG TUA TERHADAP PRESTASI AKADEMIK MAHASISWA - Amin, Sutamat; Ninghardjanti, Patni; Widodo, Jumiyanto (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2014)
The objective of this research are to investigate: (1) whether or not there is a significant relationship of learning motivation (X1) to academic achievement (Y) of economic education of SebelasMaret University,Surakartain academic year 2013/2014?; (2) whether or not there is a significant relationship of parent income level (X2) to academic achievement (Y) of economic education of SebelasMaret University,Surakarta in academic year 2013/2014?; and (3) whether or not there is a significant relationship of learning motivation (X1) and parent income level (X2) to academic achievement (Y) of economic education of SebelasMaret University Surakartain academic year 2013/2014?Theresearch used the correlational descriptive method with quantitative approach. The population was the 2011 generation-students of economic education of SebelasMaret University,Surakarta in academic year 2013/2014, consisting of 173 students. The sample consisted of 64 students and they were taken by means ofproportional random sampling technique. The data of the research were genthered through questionnaire and documentation and then analyzed using the computer program of SPSS 17..The results of the research are as follows: (1) there was a significant relationship of learning motivation (X1) to academic achievement (Y) of economic education of SebelasMaret University,Surakarta in academic year 2013/2014; (2) there was a significant relationship of parent income level (X2) to academic achievement (Y) of economic education of SebelasMaret University,Surakarta in academic year 2013/2014; and (3) there was a significant relationship of learning motivation (X1) and parent income level (X2) to academic achievement (Y) of economic education of SebelasMaret University,Surakarta in academic year 2013/2014.The linear regression equation was ? = 35.316 + 0.671 X1 + 0.548 X2. The relative contribution of (X1) variable to (Y) was 53.67% and that of (X2) variable to (Y) was 46.33%. The effective contribution of (X1) variable to (Y) was 17.78% and that of (X2) variable to (Y) was 15.35%. Keywords: motivation, income level, academic achievement.